2014
DOI: 10.1097/gme.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in women with or without hot flashes

Abstract: Hot flashes contribute differently to various variables affecting health-related quality of life shortly after menopause. Estradiol or an estradiol-medroxyprogesterone acetate combination similarly alleviates hot flashes and improves health-related quality of life in relation to elimination of hot flashes. Hormone therapy use does not confer any detectable quality-of-life benefit over placebo in women without disturbing baseline flashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Authors were contacted for 23 trials; the remaining 10 did not provide contact information. Two of 23 contacted authors provided the requested data [24, 25]. Thereafter, a total of nine trials had complete report of sleep quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors were contacted for 23 trials; the remaining 10 did not provide contact information. Two of 23 contacted authors provided the requested data [24, 25]. Thereafter, a total of nine trials had complete report of sleep quality.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the nine trials included a placebo treatment arm [15, 2429], while 2 had parallel comparisons of MHT formulations [30, 31]. Therefore, the seven RCTs with placebo arm as comparator had similar interventions and reported sufficient quantitative data to allow for statistical pooling (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasomotor symptoms (VMS) have been shown to negatively affect quality of life, increase sleep disturbances, impair social relationships, interfere with mood, and decrease work productivity, and are especially bothersome when severe. 1-9 For example, women with moderate to severe VMS have increased frequency of nighttime wakefulness 10-12 and chronic insomnia. 13 They are also more than three times more likely to report impaired quality of life than those with mild or moderate VMS.…”
mentioning
confidence: 99%
“…7 A smaller study specifically reported an association between hot flushes and poor sleep. 11 Chronic insomnia has been reported in approximately 50% to 55% of peri- and postmenopausal women versus approximately 35% of premenopausal women, with 81.3% of women with severe hot flushes experiencing symptoms of chronic insomnia. 6 Because VMS and associated symptoms, particularly sleep disruption, can lead to substantial physical and psychosocial impairment among postmenopausal women, addressing these symptoms is clinically important.…”
mentioning
confidence: 99%